Model Predictive Current Control of Grid Connected PV Systems - Satya Ravi Rai; Jaya Kumar S V; Keerthi Deepika K (Institute of Advanced Engineering and Science, 2016)
This paper deals with the design and simulation of an efficient solar photovoltaic system with a maximum power point tracking system (MPPT). Maximum power point (MPP) is obtained by using Perturb and Observe (P&O) algorithm. The output from solar panel is fed to the DC-DC (Boost) converter which steps up the output voltage. It is then fed to a 3-phase inverter. The inverter used is a 3-phase two-level inverter implemented with a Model Predictive Control strategy. Model of the system is considered in order to predict the control variables. Optimum switching state is selected by minimizing the cost function for each sampling period. This is achieved through modelling and MATLAB simulation of various stages that constitute the overall system.